A method for manufacturing explosion-proof communication cable
By spraying explosion-proof materials made of polyurea polymer and modified carbon nanotubes on the outer sheath surface of the cable, the existing explosion-proof cables are solved, and the problems of insufficient flexibility and increased weight when used on ships are solved, achieving stronger explosion-proof performance and applicability.
Patent Information
- Application Number
- CN202210915215.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-01
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-08-01
AI Technical Summary
When used on ships, existing explosion-proof cables are insufficient in flexibility and bending, and the addition of explosion-proof boards increases the weight and installation difficulty of the cable, limiting their scope of application.
A layer of explosion-proof material is sprayed on the surface of the outer sheath layer of the cable, which is made of polyurea polymer as the film forming matrix, and modified carbon nanotubes are added therein to enhance explosion-proof performance.
The explosion-proof performance, flame-retardant performance and mechanical properties of the cable are improved, making it suitable for explosion-proof occasions such as ships.
Smart Images

Figure BDA0003775399650000041 
Figure BDA0003775399650000051 
Figure BDA0003775399650000052
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of communication cables, and in particular, relates to a method for manufacturing an explosion-proof communication cable. Background Art
[0002] When using cables on ships, when the circuit is disconnected, there will be discharge in the inductive circuit. When the circuit is closed, the cable itself, as an energy storage element, stores the power energy in the form of an electric field. There will be discharge in both the capacitor and the resistor. The discharge current of the capacitor circuit will be large and the speed will be fast. The discharge energy of the spark will also be concentrated, which is extremely dangerous. If the circuit passes through the storage area of flammable and explosive materials, it is easy to cause the explosive mixture to ignite. Therefore, explosion-proof communication cables are needed.
[0003] Explosion-proof cables have been widely used in some places with explosive hazards, such as warehouses, chemical companies, gas stations, gas stations, oil companies and other places with extremely high safety requirements. In order to prevent the storm shock waves caused by the explosion from damaging the cables, as well as the electromagnetic interference between the lines and surrounding equipment, internal circular explosion-proof plates, steel wire armor, and copper wire braided shielding are mainly used to meet the requirements. The existing explosion-proof cables are realized by setting circular explosion-proof plates inside the cables, mainly steel wire armor and copper wire armor, so that the cables will not be damaged under the action of external forces. However, the use of this structure reduces the softness and flexibility of the cable; the addition of explosion-proof plates will increase the weight of the cable itself, which increases the difficulty of installation and laying on the one hand, and makes the cable only suitable for use on land, and not suitable for use on ships on the other hand.
[0004] Therefore, it is necessary to find other ways to improve the explosion-proof performance of communication cables. Summary of the invention
[0005] In view of the problems and shortcomings of the above-mentioned background technology, the present invention provides a method for manufacturing an explosion-proof communication cable.
[0006] In order to improve the explosion-proof performance of the cable, the present invention sprays a layer of explosion-proof material on the surface of the outer sheath layer of the cable. The explosion-proof material uses a polyurea polymer as a film-forming matrix, and modified carbon nanotubes are added to the polyurea for reinforcement. Specifically, firstly, the polyurea polymer has the characteristics of light weight, wear resistance, impact resistance, corrosion resistance, etc., and has strong adhesion to substrates including metals and non-metals, which can ensure long-term coating and use without falling off, and has explosion-proof performance; secondly, after the carbon nanotubes are modified, organic molecular chains are grafted on the surface, which can improve the agglomeration phenomenon of the carbon nanotubes and the interface compatibility between the carbon nanotubes and the polyurea, promote the uniform dispersion of the carbon nanotubes in the polyurea, and make the carbon nanotubes better play the role of mechanical enhancement and antistatic enhancement, thereby improving the explosion-proof performance of the cable; thirdly, the organic molecular chains grafted on the surface contain a variety of flame-retardant functional groups, have excellent flame-retardant effects, and improve the explosion-proof performance of the cable from the flame-retardant aspect; the communication cable obtained by the present invention has good flame-retardant performance, strong explosion-proof performance, and good mechanical properties, and can be suitable for explosion-proof occasions such as ships.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A method for manufacturing an explosion-proof communication cable, the communication cable comprising a conductor core, an insulating layer coated outside the conductor core, a shielding layer wrapped outside the insulating layer, a pressure-resistant layer extruded outside the shielding layer, a sheath layer coated on the pressure-resistant layer, and an explosion-proof material sprayed on the surface of the sheath layer to form an explosion-proof layer;
[0009] A method for manufacturing an explosion-proof communication cable, as follows:
[0010] An insulating layer is coated on the conductor core by an extrusion process, and then a shielding layer is formed by overlapping winding. A pressure-resistant layer is then coated on the shielding layer, and a sheath layer is coated on the pressure-resistant layer by a double extrusion process. Finally, an explosion-proof material is sprayed on the surface of the sheath layer to form an explosion-proof layer, thereby obtaining an explosion-proof communication cable.
[0011] Furthermore, the shielding layer is formed by wrapping an aluminum-plastic composite tape on a wrapping machine or a cabling machine; the pressure-resistant layer is formed by wrapping a double layer of galvanized steel tape with gaps, and the gap of the inner galvanized steel tape is covered by the outer galvanized steel tape, and the gap rate of the galvanized steel tape is not greater than 50% of the width of the galvanized steel tape; the sheath layer is formed by extruding a low-smoke, halogen-free, flame-retardant, irradiated cross-linked polyolefin on a common extruder.
[0012] Furthermore, the explosion-proof material includes component A and component B, wherein component A includes polycaprolactone polyol and isocyanate monomer; component B includes polytetramethylene ether di-p-aminobenzoate (terminated amino polyether), 3,3'-dichloro-4,4'-diphenylmethane diamine (chain extender) and modified carbon nanotubes;
[0013] The specific preparation process of explosion-proof materials is as follows:
[0014] The first step is to add polycaprolactone polyol into a nitrogen-protected reactor, heat it to 110-120°C under stirring, dehydrate it under vacuum -0.1MPa for 60-80min, release the vacuum, cool it to below 60°C, add diphenylmethane diisocyanate, heat it to 80°C, keep the temperature at 80-90°C for reaction for 2-3h, measure NCO% (18%) and discharge it after it is qualified, filter it with a 200-mesh filter to obtain component A;
[0015] Step 2: sequentially add polytetramethylene ether di-p-aminobenzoate, 3,3'-dichloro-4,4'-diphenylmethanediamine, and modified carbon nanotubes into a high-speed disperser under stirring at 600 r / min, adjust the speed to 1500 r / min after adding, mix and stir at room temperature for 60-70 min, and filter through a 200-mesh filter to obtain component B;
[0016] Step 3: When using, mix components A and B evenly to obtain explosion-proof material.
[0017] Furthermore, the mass ratio of polycaprolactone polyol, diphenylmethane diisocyanate, polytetramethylene ether di-p-aminobenzoate, 3,3'-dichloro-4,4'-diphenylmethane diamine and modified carbon nanotubes is 80:60:18:12:0.3.
[0018] A polyurea polymer is obtained with polycaprolactone polyol, diphenylmethane diisocyanate and polytetramethylene ether diparaaminobenzoate as main raw materials; the polyurea polymer has the characteristics of light weight, wear resistance, impact resistance and corrosion resistance, and has strong adhesion to substrates including metals and non-metals, can ensure long-term coating without falling off, and has explosion-proof performance.
[0019] Further, the modified carbon nanotubes are prepared by the following steps:
[0020] S1. Place carbon nanotubes in a conical flask, then add mixed acid, and ultrasonically treat in a 50°C water bath for 6 hours. After the mixture is cooled to room temperature, add deionized water to dilute, centrifuge, and wash with anhydrous ethanol and deionized water for 4-5 times in sequence, dry at 100°C to constant weight, grind through a 200-mesh sieve to obtain pretreated carbon nanotubes; the mixed acid is a mixture of 98% by mass concentrated sulfuric acid and 37.5% by mass concentrated hydrochloric acid in a volume ratio of 5:1; the ratio of carbon nanotubes to mixed acid is 1g:12mL;
[0021] By subjecting carbon nanotubes to ultrasonic shearing and oxidation treatment with strong acid, a certain number of hydroxyl and carboxyl active groups can be introduced into the side walls and tops of carbon nanotubes, laying the foundation for reaction sites for subsequent chemical reactions.
[0022] S2, phenyl dichlorophosphate and THF (tetrahydrofuran) were added to a four-necked flask with a mechanical stirring device, the temperature of the system was maintained at 25 ° C, N-methylallylamine was dissolved in THF to form a solution, and the solution was added dropwise to the four-necked flask under stirring, and the reaction was continued for 2 hours. The reaction solution was then heated to 50 ° C, and the reaction was continued for 48 hours. During the reaction, a NaOH solution with a concentration of 0.1 mol / L was used to maintain the pH above 10. After the reaction was completed, most of the THF solvent was removed by rotary evaporation, and toluene was used for multiple extractions. The organic phase was washed with a saturated NaCl aqueous solution for multiple times and then dried with anhydrous Na2SO4 for 48 hours, filtered, and concentrated under reduced pressure to obtain an intermediate; the concentration of the solute in the THF solution of N-methylallylamine was 0.156 g / mL, and the amount ratio of phenyl dichlorophosphate, THF, and the THF solution of N-methylallylamine was 21.1 g: 150 mL: 50 mL;
[0023] The -Cl on phenyl dichlorophosphate reacts chemically with the -NH- on the N-methylallylamine molecule. By controlling the molar ratio of phenyl dichlorophosphate to N-methylallylamine to be close to 1:1, only one -Cl on phenyl dichlorophosphate participates in the reaction to obtain an intermediate. The reaction process is shown below:
[0024]
[0025] S3, dissolving thioethylamine in a mixed solvent of methanol and distilled water, and then adding the mixture into a four-necked flask with a stirring device, maintaining the temperature of the system at 70°C, dissolving the intermediate and AIBN in methanol to form a solution of the intermediate, adding the mixture dropwise into the four-necked flask under stirring, and reacting at 70°C for 4 hours. After the reaction is completed, cooling to room temperature, and distilling under reduced pressure to obtain a modifier; the ratio of the amount of the intermediate, AIBN and methanol in the solution of the intermediate is 2.46g:0.21g:12mL; the ratio of the amount of thioethylamine, methanol, distilled water and the solution of the intermediate is 1.84g:100mL:10mL:120mL;
[0026] The -C=C introduced in the intermediate reacts chemically with the thiol group on the thioethylamine molecule to obtain a modifier, which contains a phosphate group, a nitrogen-containing group, a sulfur-containing group and -NH2. The specific reaction process is as follows:
[0027]
[0028] S4, dispersing the modifier in DMF, adding DCC (dicyclohexylcarbodiimide) and DMAP (4-dimethylaminopyridine), magnetically stirring for 1 hour to obtain a solution, then mixing the pretreated carbon nanotubes with the solution at a solid-liquid ratio of 1g:14mL, magnetically stirring for 2 hours, placing in a 60°C water bath for ultrasonication for 2 hours, then removing the water bath and magnetically stirring at room temperature for 24 hours, filtering, and washing with anhydrous ethanol and deionized water for 3-4 times in sequence, vacuum drying to constant weight, to obtain modified carbon nanotubes; the ratio of the amount of the modifier, DMF, DCC and DMAP in the solution is 2g:28mL:0.6g:0.05g;
[0029] Under the action of DCC and DMAP, -COOH contained on the surface of pretreated carbon nanotubes reacts chemically with -NH2 on the modifier molecules to form -CO-NH- bonds, and organic molecular chains are grafted on the surface of carbon nanotubes to obtain modified carbon nanotubes. The reaction process is as follows:
[0030]
[0031] The carbon nanotube surface grafting modifier, on the one hand, introduces organic molecular chains on the surface of carbon nanotubes through chemical bonding, which can improve the interface compatibility between carbon nanotubes (inorganic materials) and polymer matrix (polyurea), promote the uniform dispersion of carbon nanotubes in the matrix and the uniformity of the material, and in addition, the -CO-NH contained thereon has high compatibility with urea groups, further improving the interface compatibility between carbon nanotubes and polymer matrix; on the other hand, the organic molecular chains grafted on the surface of carbon nanotubes include phosphate groups, nitrogen-containing groups and sulfur-containing groups, and the phosphate groups and nitrogen-containing groups can play a synergistic flame retardant role. It should be pointed out that the S-containing group generates non-flammable gas SO2 at high temperature, and SO2 can expand the carbon layer, acting as both an acid source and a gas source, further improving the flame retardant effect of the above-mentioned organic molecules;
[0032] Carbon nanotubes themselves have high mechanical properties. Therefore, by introducing synthetic organic molecules on the surface of carbon nanotubes, it can not only promote the uniform dispersion of carbon nanotubes and enable carbon nanotubes to play a mechanical strengthening role, but also introduce flame retardant components. The introduction of flame retardant components through carbon nanotubes not only avoids the migration characteristics of flame retardants, but also reduces the uniformity problems caused by the addition of multiple different raw materials, giving the composite material better flame retardant properties. The better the flame retardant effect, the better the explosion release performance, thereby improving the explosion-proof performance of the cable. In addition, carbon nanotubes themselves are an antistatic filler that can reduce the accumulation of charge in the composite material, thereby improving the explosion-proof performance of the cable.
[0033] Beneficial effects of the present invention:
[0034] In order to improve the explosion-proof performance of the cable, the present invention sprays a layer of explosion-proof material on the surface of the outer sheath layer of the cable. The explosion-proof material uses a polyurea polymer as a film-forming matrix, and modified carbon nanotubes are added to the polyurea for reinforcement. Specifically, firstly, the polyurea polymer has the characteristics of light weight, wear resistance, impact resistance, corrosion resistance, etc., and has strong adhesion to substrates including metals and non-metals, which can ensure long-term coating and use without falling off, and has explosion-proof performance; secondly, after the carbon nanotubes are modified, organic molecular chains are grafted on the surface, which can improve the agglomeration phenomenon of the carbon nanotubes and the interface compatibility between the carbon nanotubes and the polyurea, promote the uniform dispersion of the carbon nanotubes in the polyurea, and make the carbon nanotubes better play the role of mechanical enhancement and antistatic enhancement, thereby improving the explosion-proof performance of the cable; thirdly, the organic molecular chains grafted on the surface contain a variety of flame-retardant functional groups, have excellent flame-retardant effects, and improve the explosion-proof performance of the cable from the flame-retardant aspect; the communication cable obtained by the present invention has good flame-retardant performance, strong explosion-proof performance, and good mechanical properties, and can be suitable for explosion-proof occasions such as ships. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] The modified carbon nanotubes are prepared by the following steps:
[0038] S1. Place 20 g of carbon nanotubes in a conical flask, then add 240 mL of mixed acid (200 mL of 98% by mass concentrated sulfuric acid and 40 mL of 37.5% by mass concentrated hydrochloric acid), and ultrasonically treat in a 50°C water bath for 6 h. After the mixture is cooled to room temperature, add 600 mL of deionized water to dilute, centrifuge, and wash with anhydrous ethanol and deionized water for 4 times in sequence, dry at 100°C to constant weight, and grind through a 200-mesh sieve to obtain pretreated carbon nanotubes;
[0039] S2, 21.1g of phenyl dichlorophosphate and 150mL of THF (tetrahydrofuran) were added to a four-necked flask with a mechanical stirring device, the temperature of the system was maintained at 25°C, 2.8g of N-methylallylamine was dissolved in 50mL of THF to form a solution, and the solution was added dropwise to the four-necked flask under stirring, and the reaction was continued for 2h, and the reaction solution was heated to 50°C and the reaction was continued for 48h. During the reaction, a NaOH solution with a concentration of 0.1mol / L was used to maintain the pH above 10. After the reaction was completed, most of the THF solvent was removed by rotary evaporation, and toluene was used for extraction 3 times. The organic phase was washed 3 times with a saturated NaCl aqueous solution and then dried with anhydrous Na2SO4 for 48h, filtered, and concentrated under reduced pressure to obtain an intermediate;
[0040] S3, dissolving 1.84g of thioethylamine in a mixed solvent of 100mL of methanol and 10mL of distilled water, and then adding the mixture into a four-necked flask with a stirring device, maintaining the temperature of the system at 70°C, dissolving 24.6g of the intermediate and 2.1g of AIBN in 120mL of methanol to form a solution of the intermediate, and adding the solution dropwise into the four-necked flask under stirring, and reacting at 70°C for 4h. After the reaction is completed, cooling to room temperature, and distilling under reduced pressure to obtain a modifier;
[0041] S4. Disperse 20 g of the modifier in 280 mL of DMF, add 6 g of DCC (dicyclohexylcarbodiimide) and 0.5 g of DMAP (4-dimethylaminopyridine), and stir magnetically for 1 hour to obtain a dissolved solution. Mix 20 g of the pretreated carbon nanotubes with the dissolved solution, stir magnetically for 2 hours, and then put it in a 60°C water bath for 2 hours of ultrasonic treatment. Remove the water bath and stir magnetically at room temperature for 24 hours. Filter, wash with anhydrous ethanol and deionized water three times in sequence, and vacuum dry to constant weight to obtain modified carbon nanotubes.
[0042] Example 2
[0043] The modified carbon nanotubes are prepared by the following steps:
[0044] S1. Place 40 g of carbon nanotubes in a conical flask, then add 480 mL of mixed acid (400 mL of 98% by mass concentrated sulfuric acid and 80 mL of 37.5% by mass concentrated hydrochloric acid), and ultrasonically treat in a 50°C water bath for 6 h. After the mixture is cooled to room temperature, add 800 mL of deionized water to dilute, centrifuge, and wash with anhydrous ethanol and deionized water for 5 times in sequence, dry at 100°C to constant weight, and grind through a 200-mesh sieve to obtain pretreated carbon nanotubes;
[0045] S2, 42.2g of phenyl dichlorophosphate and 300mL of THF (tetrahydrofuran) were added to a four-necked flask with a mechanical stirring device, the temperature of the system was maintained at 25°C, 5.6g of N-methylallylamine was dissolved in 100mL of THF to form a solution, and the solution was added dropwise to the four-necked flask under stirring, and the reaction was continued for 2h, and the reaction solution was heated to 50°C, and the reaction was continued for 48h. During the reaction, a NaOH solution with a concentration of 0.1mol / L was used to maintain the pH above 10. After the reaction was completed, most of the THF solvent was removed by rotary evaporation, and toluene was extracted 4 times. The organic phase was washed 4 times with a saturated NaCl aqueous solution and then dried with anhydrous Na2SO4 for 48h, filtered, and concentrated under reduced pressure to obtain an intermediate;
[0046] S3, dissolving 3.68g of thioethylamine in a mixed solvent of 200mL of methanol and 20mL of distilled water, and then adding the mixture into a four-necked flask with a stirring device, maintaining the temperature of the system at 70°C, dissolving 49.2g of the intermediate and 4.2g of AIBN in 240mL of methanol to form a solution of the intermediate, and adding the solution dropwise into the four-necked flask under stirring, and reacting at 70°C for 4h. After the reaction, cooling to room temperature, and distilling under reduced pressure to obtain a modifier;
[0047] S4. Disperse 40 g of the modifier in 560 mL of DMF, add 12 g of DCC (dicyclohexylcarbodiimide) and 1 g of DMAP (4-dimethylaminopyridine), and stir magnetically for 1 hour to obtain a dissolved solution. Mix 40 g of the pretreated carbon nanotubes with the dissolved solution, stir magnetically for 2 hours, and then put it in a 60°C water bath for 2 hours of ultrasonic treatment. Remove the water bath and stir magnetically at room temperature for 24 hours. Filter, wash with anhydrous ethanol and deionized water for 3-4 times in sequence, and vacuum dry to constant weight to obtain modified carbon nanotubes.
[0048] Example 3
[0049] The specific preparation process of explosion-proof materials is as follows:
[0050] The first step is to add 800g of polycaprolactone polyol into a nitrogen-protected reactor, heat to 110°C under stirring, dehydrate for 60min under vacuum -0.1MPa, release the vacuum, cool to below 60°C, add 600g of diphenylmethane diisocyanate, heat to 80°C, keep the temperature at 80-90°C for 2h, filter through a 200-mesh filter to obtain component A;
[0051] Step 2: 180 g of polytetramethylene ether di-p-aminobenzoate, 120 g of 3,3'-dichloro-4,4'-diphenylmethanediamine, and 3 g of modified carbon nanotubes were sequentially added into a high-speed disperser under stirring at 600 r / min, and the speed was adjusted to 1500 r / min after the feeding was completed. The mixture was mixed and stirred at room temperature for 60 min, and filtered through a 200-mesh filter to obtain component B;
[0052] Step 3: When using, mix components A and B evenly to obtain explosion-proof material.
[0053] Example 4
[0054] The specific preparation process of explosion-proof materials is as follows:
[0055] The first step is to add 1600g of polycaprolactone polyol into a nitrogen-protected reactor, heat to 120°C under stirring, dehydrate for 80min under vacuum -0.1MPa, release the vacuum, cool to below 60°C, add 1200g of diphenylmethane diisocyanate, heat to 80°C, keep the temperature at 90°C for 3h, filter through a 200-mesh filter to obtain component A;
[0056] Step 2: 360 g of polytetramethylene ether di-p-aminobenzoate, 240 g of 3,3'-dichloro-4,4'-diphenylmethanediamine, and 6 g of modified carbon nanotubes were sequentially added into a high-speed disperser under stirring at 600 r / min, and the speed was adjusted to 1500 r / min after the feeding was completed. The mixture was mixed and stirred at room temperature for 70 min, and filtered through a 200-mesh filter to obtain component B;
[0057] Step 3: When using, mix components A and B evenly to obtain explosion-proof material.
[0058] Comparative Example 1
[0059] The modified carbon nanotubes in Example 3 are replaced with ordinary carbon nanotubes, and the other raw materials and preparation process remain unchanged to obtain an explosion-proof material.
[0060] The explosion-proof materials obtained in Examples 2-3 and Comparative Example 1 were sampled using a portable static mixing spraying device and subjected to relevant performance tests after curing for 7 days under standard conditions:
[0061] The tensile properties (tensile strength and elongation at break) were tested according to GB / T528-2009; the tearing properties were tested according to GB / T529-2008;
[0062] Determine the oxygen index of the sample; test the volume resistivity of the material;
[0063] Test the explosion-proof performance: Use 1.2kgTNT impact to observe the damage of the coating;
[0064] The measured results are shown in the following table:
[0065]
[0066] It can be seen from the data in the above table that the explosion-proof material obtained by the present invention has higher mechanical properties and flame retardant properties, higher explosion-proof performance, and certain antistatic properties.
[0067] Example 5
[0068] A method for manufacturing an explosion-proof communication cable, as follows:
[0069] An insulating layer is coated on the conductor core by an extrusion process, and then an aluminum-plastic composite tape is wrapped on a wrapping machine or a cabling machine to form a shielding layer, and then a pressure-resistant layer is coated on the shielding layer, and a low-smoke, halogen-free, flame-retardant, radiation-crosslinked polyolefin is extruded on a common extruder to coat the pressure-resistant layer with a sheath layer, and finally the explosion-proof material prepared in Example 3 is sprayed on the surface of the sheath layer to form an explosion-proof layer, thereby obtaining an explosion-proof communication cable;
[0070] The pressure-resistant layer is formed by wrapping a double layer of galvanized steel strips with gaps, and the gaps of the inner galvanized steel strips are covered by the outer galvanized steel strips, and the gap rate of the galvanized steel strips is not greater than 50% of the width of the galvanized steel strips.
[0071] Example 6
[0072] A method for manufacturing an explosion-proof communication cable, as follows:
[0073] An insulating layer is coated on the conductor core by an extrusion process, and then an aluminum-plastic composite tape is wrapped on a wrapping machine or a cabling machine to form a shielding layer, and then a pressure-resistant layer is coated on the shielding layer, and a low-smoke, halogen-free, flame-retardant, radiation-crosslinked polyolefin is extruded on a common extruder to coat the pressure-resistant layer with a sheath layer, and finally the explosion-proof material prepared in Example 4 is sprayed on the surface of the sheath layer to form an explosion-proof layer, thereby obtaining an explosion-proof communication cable;
[0074] The pressure-resistant layer is formed by wrapping a double layer of galvanized steel strips with gaps, and the gaps of the inner galvanized steel strips are covered by the outer galvanized steel strips, and the gap rate of the galvanized steel strips is not greater than 50% of the width of the galvanized steel strips.
[0075] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.
Claims
1. A method for manufacturing explosion-proof communication cables, which is as follows: an insulating layer is coated on the outside of a conductor core by an extrusion process, a shielding layer is formed by overlapping wrapping, a pressure-resistant layer is coated on the outside of the shielding layer, a sheath layer is coated on the pressure-resistant layer by a double extrusion process, and finally an explosion-proof material is sprayed on the surface of the sheath layer to form an explosion-proof layer, characterized in that: The explosion-proof material comprises component A and component B, wherein component A comprises polycaprolactone polyol and isocyanate monomer; component B comprises polytetramethylene ether di-p-aminobenzoate, 3,3'-dichloro-4,4'-diphenylmethanediamine and modified carbon nanotubes; Wherein, the modified carbon nanotubes are prepared by the following steps: S1. Place carbon nanotubes in a conical flask, then add mixed acid, and ultrasonically treat in a 50°C water bath for 6 hours. After the mixture is cooled to room temperature, add deionized water to dilute, centrifuge, and wash with anhydrous ethanol and deionized water for 4-5 times in sequence, dry at 100°C to constant weight, and grind through a 200-mesh sieve to obtain pretreated carbon nanotubes; S2, adding phenyl dichlorophosphate and tetrahydrofuran to a four-necked flask with a mechanical stirring device, maintaining the temperature of the system at 25°C, dissolving N-methylallylamine in tetrahydrofuran to form a solution, adding dropwise to the four-necked flask under stirring, reacting for 2h, then heating the reaction solution to 50°C, and continuing the reaction for 48h. During the reaction, using NaOH solution to maintain the pH above 10, after the reaction is completed, rotary evaporation, extraction with toluene for multiple times, washing the organic phase with saturated NaCl aqueous solution for multiple times, and then drying with anhydrous Na2SO4 for 48h, filtering, and concentrating under reduced pressure to obtain an intermediate; S3, dissolving thioethylamine in a mixed solvent of methanol and distilled water, and then adding the mixture into a four-necked flask with a stirring device, maintaining the temperature of the system at 70°C, dissolving the intermediate and AIBN in methanol to form a solution of the intermediate, and adding the solution dropwise into the four-necked flask under stirring, and reacting at 70°C for 4 hours. After the reaction is completed, cooling to room temperature, and distilling under reduced pressure to obtain a modifier; S4, dispersing the modifier in DMF, adding dicyclohexylcarbodiimide and 4-dimethylaminopyridine, magnetically stirring for 1 hour to obtain a solution, then mixing the pretreated carbon nanotubes with the solution at a solid-liquid ratio of 1g:14mL, magnetically stirring for 2 hours, placing in a 60°C water bath for 2 hours, then removing the water bath and magnetically stirring at room temperature for 24 hours, filtering, and washing with anhydrous ethanol and deionized water for 3-4 times in sequence, and vacuum drying to constant weight to obtain modified carbon nanotubes; The specific preparation process of explosion-proof materials is as follows: Step 1: Add polycaprolactone polyol to a nitrogen-protected reactor, heat to 110-120°C under stirring, dehydrate for 60-80 min under vacuum -0.1MPa, release the vacuum, cool to below 60°C, add diphenylmethane diisocyanate, heat to 80°C, keep the temperature at 80-90°C for 2-3h, discharge after NCO% is qualified, filter with 200 mesh filter to obtain component A; Step 2: sequentially add polytetramethylene ether di-p-aminobenzoate, 3,3'-dichloro-4,4'-diphenylmethanediamine, and modified carbon nanotubes into a high-speed disperser under stirring at 600 r / min, adjust the speed to 1500 r / min after adding, mix and stir at room temperature for 60-70 min, and filter through a 200-mesh filter to obtain component B; Step 3: When using, mix components A and B evenly to obtain explosion-proof material.
2. The method for manufacturing an explosion-proof communication cable according to claim 1, characterized in that: The mass ratio of polycaprolactone polyol, diphenylmethane diisocyanate, polytetramethylene ether di-p-aminobenzoate, 3,3'-dichloro-4,4'-diphenylmethane diamine and modified carbon nanotubes is 80:60:18:12:0.
3.
3. The method for manufacturing an explosion-proof communication cable according to claim 1, characterized in that: In step S1, the mixed acid is a mixture of 98% by mass concentrated sulfuric acid and 37.5% by mass concentrated hydrochloric acid in a volume ratio of 5:1; the ratio of the carbon nanotubes to the mixed acid is 1 g:12 mL.
4. The method for manufacturing an explosion-proof communication cable according to claim 1, characterized in that: In step S2, the concentration of the solute in the tetrahydrofuran solution of N-methylallylamine is 0.156 g / mL, and the amount ratio of phenyl dichlorophosphate, tetrahydrofuran, and the tetrahydrofuran solution of N-methylallylamine is 21.1 g:150 mL:50 mL.
5. The method for manufacturing an explosion-proof communication cable according to claim 1, characterized in that: In step S3, the ratio of the intermediate, AIBN and methanol in the solution of the intermediate is 2.46 g:0.21 g:12 mL; the ratio of thioethylamine, methanol, distilled water and the solution of the intermediate is 1.84 g:100 mL:10 mL:120 mL.
6. The method for manufacturing an explosion-proof communication cable according to claim 1, characterized in that: The ratio of the amount of the modifier, DMF, dicyclohexylcarbodiimide and 4-dimethylaminopyridine in the dissolving solution in step S4 is 2 g:28 mL:0.6 g:0.05 g.
Citation Information
Patent Citations
Flame-retardant polyurea anti-explosion protective material and preparation method thereof
CN111499834A
High-strength internal shielding railway digital signal cable
CN112700912A